An Irigarayan reading of selected novels of Emily and Charlotte Brontë, Alice Walker and Anaïs Nin / Shiva Hemmati - Shiva , Hemmati (2018)
Though Irigaray’s theories of ‘feminine divine’ and ‘sexual difference’ have been discussed by many feminist scholars, I found Irigaray-inspired notions of non-duality within duality remarkably interesting in reading women novelists’ works from different ages, namely, Emily Brontë’s Wuthering Heights (1847), Charlotte Brontë’s Jane Eyre (1848), Alice Walker’s The Color Purple (1982), and Anaïs Nin’s A Spy in the House of Love (1954), in terms of exploring women’s self-consciousness and liberation. In exploring non-duality within the dualities of body/mind, self/other, and male/female, this study is grounded on Irigaray’s notions of ‘feminine jouissance,’ ‘feminine divine,’ ‘sexual difference,’ ‘sensible transcendental,’ and love, which are interrelated throughout her work. Irigaray’s concepts introduce female body as divine, and challenge the established dualities and the oppressive male-dominated structure of patriarchal society. My reading of non-duality within duality through Irigarayan concepts in the selected novels introduces alternative ways of approaching women’s subjectivity, self-realization, and self-consciousness, and offers a new insight in the analysis of the gendered experiences of female characters. It shows how the rebellious female characters struggle with the hierarchical traditional dualities of the patriarchal world and challenge social knowledge about women. While the female protagonists in Emily Brontë and Anaïs Nin’s novels are entrapped within the defined dualities of the patriarchal world, the female characters in Charlotte Brontë and Alice Walker’s novels counter the traditional dualities, speak clearly of their female desires and experiences within the social constraints, and achieve autonomous subjectivity, self-consciousness, reciprocal love, and liberation within the oppressive structure of patriarchal society. These female characters are successful when they discover their self beyond the traditional dualities of the patriarchal world through their love affairs.